Needs analysis to develop teaching materials at Vocational College UGM - Yohana Ika Harnita Sari; Wahyu Kartika Wienanda; Nur Endah Nugraheni (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2020)
Needs analysis as an initial process in a course becomes crucial before deciding learning objectives, setting the assessment, creating course design, as well as developing materials. This study aims to describe the English competence and skills needed by the stakeholders and students' perceptions of good teaching materials from various study programs at Vocational College UGM. The methods used in collecting data are questionnaires and interviews. The questionnaire is distributed to the first semester students from all applied bachelor programs in Vocational College UGM using a stratified random sampling method. In addition, the interview is done with all heads of applied bachelor programs in Vocational College UGM for triangulation. The results show that the students are in the beginner level or basic users (A2 level in Common European Framework of Reference for Languages or CEFR). Moreover, the competencies stated in the A2 level are considered needed by the students to master in academic and work-life contexts. Besides, the skill considered as the most important is speaking, followed by writing. The students also propose some criteria of good teaching materials that include the content, sequence, exercise, language features, technology, layout, and price.